Perovskite solar cell of waterproof rubber composite nano metal array electrode and preparation method of perovskite solar cell

By adopting a waterproof rubber composite nanometal array electrode structure in perovskite solar cells, the sensitivity of perovskite solar cells to water and oxygen is solved, and the long-term operation stability and efficient performance of the battery are achieved.

CN119836117APending Publication Date: 2025-04-15NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967282.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The sensitivity of perovskite solar cells to water and oxygen leads to their performance degradation, hindering their commercial applications.

Method used

Using a waterproof rubber composite nanometal array electrode structure, array holes are formed in the rubber layer through nanoimprinting technology, and metal electrodes are deposited on the holes and the surface of the rubber layer to form a nano-scale metal array electrode that penetrates the entire rubber layer.

Benefits of technology

Effectively isolate moisture and oxygen in the air, improve the water and oxygen stability of perovskite solar cells, and ensure the long-term operation stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836117A_ABST
    Figure CN119836117A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and discloses a perovskite solar cell structure of a waterproof rubber metal composite electrode and a preparation method of the perovskite solar cell structure. The structure of the perovskite solar cell comprises a transparent conductive glass substrate, a charge (electron / hole) transmission layer, a perovskite layer, a charge (hole / electron) transmission layer and a waterproof rubber metal composite electrode. When the cell is prepared, the charge transfer layer, the perovskite layer, the charge transfer layer and the rubber layer need to be prepared on the transparent conductive glass in sequence, then the nano-imprinting technology is utilized to penetrate through the rubber layer to form a nano-array hole structure, and finally metal is deposited to realize the composite electrode. The main body part of the composite electrode is a rubber layer, and the rubber layer comprises a metal array which is longitudinally electrically conducted and has a nano aperture, so that the composite electrode has a good water and oxygen isolation effect while the conductivity is ensured. The prepared perovskite solar cell can resist erosion of water and oxygen in air, a new thought is provided for solving the stability problem of the perovskite solar cell, and commercial application of the perovskite technology is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solar cells, and particularly relates to a perovskite solar cell with a waterproof rubber composite nano-metal array electrode, the structure of which includes a transparent conductive glass substrate, a charge (electron / hole) transport layer, a perovskite layer, a charge (hole / electron) transport layer, and a waterproof rubber metal composite electrode. To prepare the battery, a charge transport layer, a perovskite layer, a charge transport layer, and a rubber layer need to be prepared in sequence on the transparent conductive glass, and then the nano-imprinting technology is used to penetrate the rubber layer to form a nano-array hole structure, and finally metal is deposited to realize a composite electrode. The waterproof rubber metal composite electrode can isolate moisture and oxygen in the air environment, and the battery prepared with this structure has good water-oxygen stability. Background Art

[0002] Since the first industrial revolution, humans have been using fossil energy on a large scale for more than 200 years. Due to the continuous development of the economy, the use of fossil energy has continued to increase. At present, the climate change and environmental problems caused by the burning of fossil energy cannot be ignored. Fossil energy is a primary energy source and cannot be regenerated in a short period of time. Therefore, the development of clean energy is the only way to achieve sustainable development.

[0003] As a new type of solar cell, perovskite solar cells have experienced less than 10 years of development, and their photoelectric conversion efficiency has rapidly increased to 26%, showing great development potential. Compared with other solar cells, they have the following advantages: 1. High conversion efficiency. The theoretical conversion efficiency of perovskite solar cells is as high as 31%, showing its great potential in commercial applications. 2. Low-cost preparation: Compared with traditional silicon-based solar cells, the preparation method of perovskite solar cells is simpler and less expensive. Perovskite materials can be prepared on substrates by water bath, spin coating and other methods, and are more adaptable. 3. Adjustable material properties: The chemical composition and crystal structure of perovskite materials can be regulated by controlling the ion composition and material preparation process, thereby changing their electrical and optical properties.

[0004] Although perovskite solar cells have these advantages, perovskite materials are unstable and highly sensitive to factors such as water and oxygen. Water molecules can quickly and easily form hydrogen bonds with non-coordinated iodine atoms on the surface of perovskite, and water vapor penetrates the perovskite surface and the boundary of the perovskite structure to form a reversible intermediate product MAPbl. 3 -H 2 O and MAPbl 3 -2H 2 O hydrated substances can weaken the bond between organic cations and inorganic Pbl through the strong hydrogen bond between water and organic cations. 6The bonding between the scaffolds promotes the decomposition of perovskite materials. Oxygen molecules react with perovskites to form highly reactive photoinduced superoxides, which make organic cations (such as MA + ) is deprotonated to produce water, MA, l 2 and Pbl 2 Water and oxygen will eventually lead to a decline in the performance of the entire cell, hindering the commercial application of perovskite solar cells. Summary of the invention

[0005] A perovskite solar cell with a waterproof rubber composite nano-metal array electrode comprises a transparent conductive glass substrate, a charge transport layer (electrons / holes), a perovskite layer, a charge transport layer (holes / electrons), and a waterproof rubber composite nano-metal array electrode which are stacked in sequence.

[0006] Furthermore, in the waterproof rubber composite nano-metal array electrode perovskite solar cell, array holes are formed on the formed waterproof rubber layer using nanoimprinting technology, metal is deposited in the array holes and on the surface of the rubber layer, and the rubber layer is filled with metal electrodes that penetrate the entire layer.

[0007] Furthermore, in the waterproof rubber composite nano-metal array electrode perovskite solar cell, the metal array runs through the entire rubber layer, and the two ends of the metal array are respectively connected to the charge transfer layer (holes / electrons) and the metal electrode deposited on the surface of the rubber layer.

[0008] Furthermore, the transverse diameter of each hole in the rubber layer is 5nm to 5μm. The size of the transverse diameter of the hole plays an important role in the effect of the rubber layer isolating water and oxygen. The larger the diameter, the easier it is for water and oxygen to penetrate the rubber layer. If the diameter is too small, the conductive properties of the battery will be affected.

[0009] A method for preparing a perovskite solar cell with a waterproof rubber composite nano-metal array electrode comprises the following steps:

[0010] (1) On a transparent conductive substrate, a charge transport layer (electron / hole), a perovskite layer, and a charge transport layer (hole / electron) are sequentially prepared;

[0011] (2) preparing a rubber layer on the charge transport layer (holes / electrons);

[0012] (3) preparing an array of holes on the rubber layer that penetrate the entire rubber layer;

[0013] (4) depositing metal electrodes in the array holes and on the surface of the rubber layer;

[0014] (5) Obtain perovskite solar cells with waterproof rubber composite nanometal array electrodes.

[0015] Furthermore, the rubber layer of the waterproof rubber composite nano-metal array electrode is made by spin coating, coating, and spraying, and the array holes are prepared by nano-imprinting technology.

[0016] Furthermore, the waterproof rubber composite nano-metal array electrode perovskite solar cell has a rubber layer thickness of 1 to 1000 μm, a conductive glass substrate film thickness of 10 nm to 1 μm, an electron transport layer thickness of 1 to 200 nm, a perovskite film layer thickness of 200 to 1500 nm, and a hole transport layer thickness of 1 to 200 nm. The thicker the rubber layer, the better the performance. If it is too thick, the electrode will be discontinuous, affecting conductivity.

[0017] Furthermore, in the waterproof rubber composite nano-metal array electrode perovskite solar cell, the total area of ​​the designed metal array is no more than 20% of the entire rubber layer area. Since the metal electrode cannot be dense and continuous, it can prevent the attachment and penetration of water and oxygen.

[0018] Furthermore, the transparent conductive substrate is indium tin oxide transparent conductive glass (ITO) or fluorine-doped SnO 2 Transparent conductive glass (FTO); the electron transport layer is made of TiO 2 SnO 2 、ZnO、Al 2 O 3 , Cds, fullerene and its derivatives; the perovskite layer is ABX x Y 3-x , A is CH 3 NH 2 (MA), CH 4 N 2 (FA) or Cs; B is Cu, Ni, Fe, Co, Mn, Cr or Cd; X and Y are I, Br or Cl; the hole transport layer is 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD); the metal electrode is Au or Ag; the rubber layer is styrene-butadiene rubber, butadiene rubber, isoprene rubber, chloroprene rubber, butyl rubber, nitrile rubber, ethylene-propylene rubber, silicone rubber, fluororubber, polyurethane rubber, polyacrylate rubber, chlorosulfonated polyethylene rubber, chloroether rubber or chlorinated polyethylene rubber.

[0019] Compared with the prior art, the present invention has the following beneficial effects: the nano-scale metal array electrode that runs through the entire rubber layer enables the electrons generated by the perovskite solar cell to pass through the rubber layer to generate current; and because the rubber is composed of a polymer, its molecular chain has a high degree of flexibility and ductility, so that the rubber has an extremely high compactness, and at the same time, the molecular chain of the rubber contains non-polar groups, which are not easy to interact with water and oxygen, and can effectively block the entry of water and oxygen. Therefore, the waterproof rubber composite nano-metal array electrode structure of the present invention not only ensures the battery performance, but also plays a role in blocking water and oxygen, which is conducive to achieving the long-term operation stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell of Example 1.

[0021] Figure 2 It is a schematic diagram of the structure of the perovskite solar cell of Example 2.

[0022] Figure 3 It is a schematic diagram of the structure of the perovskite solar cell of Example 3. DETAILED DESCRIPTION

[0023] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0024] Example 1

[0025] Prepare 1 ml of lead iodide solution, a solvent ratio of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) of 4:1, 1 ml of formamidine hydroiodide (FAI) / methylammonium chloride (MACl) solution, 1 ml of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) solution and butyl rubber membrane-forming solution.

[0026] Clean a 10 nm thick indium tin oxide transparent conductive glass substrate, and use a detergent, water, ethanol, and water to clean the conductive glass substrate in sequence, each time for 20 minutes, to obtain a transparent conductive glass with a clean surface, and then treat it with ozone in a UV ozone treatment machine for 20 minutes.

[0027] The titanium tetrachloride solution was prepared and heated in a water bath at 80°C for 60 minutes to obtain a uniform titanium oxide film with a thickness of 200 nm.

[0028] The film was treated with ozone for 20 minutes under the ultraviolet lamp of an ultraviolet ozone treatment machine, and a lead iodide solution was spin-coated on the titanium oxide film by spin coating at a rotation speed of 2000 rpm for 40 seconds, and then annealed on a hot stage at 80° C. for 3 minutes to obtain a lead iodide film.

[0029] The FAI solution was spin-coated on the lead iodide film by spin coating at a rotation speed of 3000 rpm for 40 seconds, and then annealed on a hot stage at 160°C for 20 minutes to obtain a 1300 nm thick perovskite film.

[0030] The Spiro-OMeTAD solution was spin-coated on the perovskite film by spin coating at a rotation speed of 3000 rpm for 40 seconds to obtain a 200 nm thick and uniform Spiro-OMeTAD film.

[0031] The butyl rubber film-forming liquid was spin-coated on the hole transport layer at a rotation speed of 2000 rpm for 40 seconds, and then placed at 50° C. for 60 minutes to evaporate the solvent and obtain a butyl rubber layer with a thickness of 1000 μm.

[0032] A 1000 μm long array columnar template is designed in advance, and the template and the manufactured substrate are bonded together under pressure at 100°C, solidified into shape, and then cooled and demolded.

[0033] Gold electrodes are prepared on the prepared battery surface and in the array holes by vacuum evaporation.

[0034] Example 2

[0035] Clean a 100 nm thick indium tin oxide transparent conductive glass substrate, and use a detergent, water, ethanol, and water to clean the conductive glass substrate in sequence, each time for 20 minutes, to obtain a transparent conductive glass with a clean surface, and then treat it with ozone in a UV ozone treatment machine for 20 minutes.

[0036] A PTAA solution (25 mg PTAA dissolved in 5 mL chlorobenzene) was prepared and the PTAA solution was spin-coated on the transparent conductive glass by spin coating at a rotation speed of 6000 rpm for 30 seconds to obtain a 100 nm thick uniform PTAA film.

[0037] Prepare 1 ml of lead iodide / formamidine hydroiodide solution, the solvent ratio of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is 9:1, and obtain the perovskite precursor solution. Spin-coat the perovskite precursor solution on the PTAA film at a speed of 3500 rpm for 30 seconds. In the 5th second after the start of spin coating, quickly add 150 ml of chlorobenzene, and then anneal on a hot stage at 100°C for 10 minutes to obtain a 700 nm thick perovskite film.

[0038] The C layer with a thickness of 100 nm was deposited by thermal evaporation. 60 Electron transport layer.

[0039] The butyl rubber film-forming liquid was spin-coated on the hole transport layer by spin coating at a rotation speed of 3000 rpm for 40 seconds, and placed at 50° C. for 60 minutes to evaporate the solvent and obtain a butyl rubber layer with a thickness of 100 μm.

[0040] A 100 μm long array columnar template is designed in advance, and the template and the manufactured substrate are bonded together under pressure at 100°C, solidified into shape, and then cooled and demolded.

[0041] Silver electrodes are prepared on the prepared battery surface and in the array holes by vacuum evaporation.

[0042] Example 3

[0043] Prepare 1 ml of lead iodide solution, a solvent ratio of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) of 4:1, 1 ml of formamidine hydroiodide (FAI) / methylammonium chloride (MACl) solution, 1 ml of 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) solution and butyl rubber membrane-forming solution.

[0044] Clean a 1 μm thick indium tin oxide transparent conductive glass substrate, and use a detergent, water, ethanol, and water to clean the conductive glass substrate in sequence, each time for 20 minutes, to obtain a transparent conductive glass with a clean surface, and then treat it with ozone in a UV ozone treatment machine for 20 minutes.

[0045] The titanium tetrachloride solution was prepared and heated in a water bath at 80°C for 40 minutes to obtain a 5 nm thick uniform titanium oxide film.

[0046] The film was treated with ozone for 20 minutes under the ultraviolet lamp of an ultraviolet ozone treatment machine, and a lead iodide solution was spin-coated on the titanium oxide film by spin coating at a rotation speed of 3000 rpm for 40 seconds, and then annealed on a hot stage at 80° C. for 3 minutes to obtain a lead iodide film.

[0047] The FAI solution was spin-coated on the lead iodide film by spin coating at a rotation speed of 4000 rpm for 40 seconds, and then annealed on a hot stage at 160°C for 20 minutes to obtain a 200 nm thick perovskite film.

[0048] The Spiro-OMeTAD solution was spin-coated on the perovskite film by spin coating at a rotation speed of 4000 rpm for 40 seconds to obtain a 20 nm thick and uniform Spiro-OMeTAD film.

[0049] The butyl rubber film-forming liquid was spin-coated on the hole transport layer by spin coating at a rotation speed of 4000 rpm for 40 seconds, and placed at 50° C. for 60 minutes to evaporate the solvent and obtain a butyl rubber layer with a thickness of 10 μm.

[0050] A 10 μm long array columnar template is designed in advance, and the template and the manufactured substrate are bonded together under pressure at 100°C, solidified into shape, and then cooled and demolded.

[0051] Gold electrodes were prepared on the prepared battery surface and in the array holes by magnetron sputtering.

Claims

1. A perovskite solar cell with a waterproof rubber composite nanometal array electrode, comprising a transparent conductive glass substrate, a charge (electron / hole) transport layer, a perovskite layer, a charge (hole / electron) transport layer, and a waterproof rubber composite nanometal array electrode stacked in sequence.

2. A method for preparing a waterproof rubber composite nano-metal array electrode perovskite solar cell. It is characterized in that: The following steps are involved: (1) On a transparent conductive glass substrate, a charge (electron / hole) transport layer, a perovskite layer and a charge (hole / electron) transport layer are sequentially prepared; (2) preparing a completely covered waterproof rubber layer on the charge (hole / electron) transport layer; (3) using nano-imprinting technology to form array holes of nanometer to micrometer scale on the waterproof rubber layer; (4) Depositing metal (such as gold or silver) that penetrates the rubber layer longitudinally in the array holes and on the surface of the rubber layer; (5) Obtain perovskite solar cells with waterproof rubber composite nanometal array electrodes.

3. According to the waterproof rubber composite nano-metal array electrode perovskite solar cell of claim 1, the metal array is characterized in that it runs through the entire rubber layer, and the two ends of the metal array are respectively connected to the charge (hole / electron) transport layer and the metal electrode.

4. According to the waterproof rubber composite nano-metal array electrode perovskite solar cell of claim 1, the lateral diameter of each hole is 5nm to 5μm.

5. According to the waterproof rubber composite nano-metal array electrode perovskite solar cell of claim 4, the designed total area of ​​the metal array accounts for no more than 20% of the area of ​​the entire rubber layer.

6. The waterproof rubber composite nano-metal array electrode perovskite solar cell according to claim 1, characterized in that: The rubber layer is prepared by spin coating, coating, spraying and the like, and the array holes are prepared by nanoimprinting technology.

7. According to the waterproof rubber composite nano-metal array electrode perovskite solar cell described in claim 1, the thickness of the rubber layer is 1 to 1000 μm, the thickness of the conductive glass substrate is 10 nm to 1 μm, the thickness of the electron transport layer is 1 to 200 nm, the thickness of the perovskite layer is 200 to 1500 nm, and the thickness of the hole transport layer is 1 to 200 nm.

8. The waterproof rubber composite nano-metal array electrode perovskite solar cell according to claim 2, characterized in that: The transparent conductive substrate is indium tin oxide transparent conductive glass (ITO) or fluorine-doped tin oxide transparent conductive glass (FTO); the material of the electron transport layer is TiO2, SnO2, ZnO, Al2O3, CdS, fullerene and its derivatives; the perovskite layer is ABX x Y 3-x , A is CH3NH2(MA), CH4N2(FA) or Cs; B is Cu, Ni, Fe, Co, Mn, Cr or Cd; X and Y are I, Br or Cl; The hole transport layer is 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD); the metal electrode is Au or Ag; the rubber layer is styrene-butadiene rubber, butadiene rubber, isoprene rubber, chloroprene rubber, butyl rubber, nitrile rubber, ethylene-propylene rubber, silicone rubber, fluororubber, polyurethane rubber, polyacrylate rubber, chlorosulfonated polyethylene rubber, chloroether rubber or chlorinated polyethylene rubber.